"CONSIDERABLE STRESS and MISERY": A first-year music teacher's experiences. (April 2019) - Stringham, David A.; Snell, Alden H.
Preparing, inducting, mentoring, and retaining new music teachers remain concerns in our profession. This article began as a study of first-year music teachers who made regular entries in secure electronic journals and participated in mid- and end-of-year interviews. We initially sought to understand these new teachers' experiences related to mentoring, professional development, collaboration, and standards-based instruction. Findings related to these topics were eclipsed, however, by challenging experiences that Elise, a first-year instrumental music teacher who participated in our study, reported. We used a narrative inquiry methodology to present Elise's experiences in context of literature related to workplace incivility, gender, hierarchical structures, and emphasis on performance in instrumental music education. Based on findings, we offer recommendations for future research related to four stakeholder groups: pre-service teachers, early career in-service teachers, experienced in-service teachers, and administrators.